Effects of Adaptogens on the Central Nervous System and the Molecular Mechanisms Associated with Their Stress-Protective Activity - Georg Wikman; Alexander Panossian (MDPI AG, 2010)
Adaptogens were initially defined as substances that enhance the "state of nonspecific resistance" in stress, a physiological condition that is linked with various disorders of the neuroendocrine-immune system. Studies on animals and isolated neuronal cells have revealed that adaptogens exhibit neuroprotective, anti-fatigue, antidepressive, anxiolytic, nootropic and CNS stimulating activity. In addition, a number of clinical trials demonstrate that adaptogens exert an anti-fatigue effect that increases mental work capacity against a background of stress and fatigue, particularly in tolerance to mental exhaustion and enhanced attention. Indeed, recent pharmacological studies of a number of adaptogens have provided a rationale for these effects also at the molecular level. It was discovered that the stress-protective activity of adaptogens was associated with regulation of homeostasis via several mechanisms of action, which was linked with the hypothalamic-pituitary-adrenal axis and the regulation of key mediators of stress response, such as molecular chaperons (e.g., HSP70), stress-activated c-Jun N-terminal protein kinase 1 (JNK1), Forkhead box O (FOXO) transcription factor DAF-16, cortisol and nitric oxide.